2017
DOI: 10.33233/fb.v11i5.1418
|View full text |Cite
|
Sign up to set email alerts
|

Prevalência da incontinência urinária em gestantes e puérperas em maternidades públicaS

Abstract: Objetivos: Conhecer a prevalência de IU entre gestantes e puérperas assistidas em maternidades públicas de Goiânia/GO e avaliar se variáveis sociodemográfi cas, a paridade, o tipo de parto, a ocorrência de episiotomia e o índice de massa corporal antes da gestação infl uenciam na ocorrência da IU. Material e métodos: Estudo descritivo transversal. Foram entrevistadas 200 puérperas internadas em maternidades públicas de baixo risco, de fevereiro a junho de 2009 e coletados dados sociodemográfi cos, referentes à… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
4
1
13

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(18 citation statements)
references
References 29 publications
0
4
1
13
Order By: Relevance
“…Figueiredo et al (2008) observed in their study a high prevalence of the use of intimate protectors and justified that this fact was probably aimed at reducing the discomfort caused by urinary loss. In contrast to this study, Martins, Sousa and Salgado (2010) observed in their study the low use of intimate protectors to reduce the discomfort caused by urinary loss during pregnancy and puerperium. This same study also shows that this habit observed in the participants can portray their strategies of how they face urinary loss, indicating the need to use or not use intimate protectors or to modify their daily activities.…”
Section: Resultas and Discussioncontrasting
confidence: 86%
See 1 more Smart Citation
“…Figueiredo et al (2008) observed in their study a high prevalence of the use of intimate protectors and justified that this fact was probably aimed at reducing the discomfort caused by urinary loss. In contrast to this study, Martins, Sousa and Salgado (2010) observed in their study the low use of intimate protectors to reduce the discomfort caused by urinary loss during pregnancy and puerperium. This same study also shows that this habit observed in the participants can portray their strategies of how they face urinary loss, indicating the need to use or not use intimate protectors or to modify their daily activities.…”
Section: Resultas and Discussioncontrasting
confidence: 86%
“…Regarding lifestyle habits, studies carried out by Martins et al (2010) and Ebbesen et al (2013) showed that smoking predisposes to the emergence of UI during pregnancy. This finding can be explained by the consequences that smoking can cause, including coughing.…”
Section: Resultas and Discussionmentioning
confidence: 99%
“…A incontinência urinária (IU) é um fenômeno bastante presente no período gestacional com uma estimativa de aproximadamente 75%, mas que pode variar em razão do tipo de estudo desenvolvido, do período investigado, bem como das características socioculturais de uma população. 10 Corroborando com esse raciocínio o estudo de Santini et al 11 , das 950 mulheres entrevistadas, 472 apresentaram alguma queixa de perda de urina, assumindo uma prevalência de 49,68% de IU, sendo grande parte IU do tipo mista e com maior incidência no terceiro trimestre de gestação.…”
Section: Resultsunclassified
“…Martins (3), when investigating 200 puerperal women, noticed that the prevalence of UI during gestation was of 47.5%. All of them referred to at least one episode of involuntary urine leakage at some point of gestation.…”
Section: Resultsmentioning
confidence: 99%
“…In this period, the pelvic floor muscles suffer a long resistance test and are extremely requested in the body changes. However, such prevalence can increase if there are repeated pregnancies, due to the obstetrical traumas (3).…”
Section: Introductionmentioning
confidence: 99%